Physiological responses and productivity of spinach (Amaranthus tricolor L.; Amaranthaceae) under monoculture and polyculture systems of urban home garden in Yogyakarta - Malika Azzahra; Siti Nurul Rofiqo Irwan; Budiastuti Kurniasih (LPPM Universitas Negeri Jakarta, 2026)
Spinach (Amaranthus tricolor L.) is an adaptive leafy vegetable suitable for cultivation in urban limited space of home garden (pekarangan). Studies comparing growth responses and productivity of green spinach and red spinach under monoculture and polyculture systems in pekarangan remain scarce. This study aimed to (1) assess growth responses and yield of green spinach and red spinach under monoculture and polyculture systems, and (2) assess the effectiveness of these systems. The experiment was conducted in pekarangan in Pilahan, Rejowinangun, Yogyakarta, from February to March 2025 using a 2×2 factorial Randomised Complete Block Design (RCBD) with three replications. Variables measured included plant height, leaf number, leaf area, biomass, chlorophyll content, and productivity. Results indicated that monoculture and polyculture systems did not significantly influence most growth and productivity parameters. Both spinach cultivars showed similar adaptability under urban hot conditions. Land Equivalent Ratio (LER) analysis revealed that polyculture achieved an LER of 1.09, reflecting a 9% increase in land-use efficiency compared to monoculture. These findings suggest polyculture has potential for application in urban pekarangan to enhance land-use efficiency and crop productivity.